Analisis implementasi metode peta konsep dalam pembelajaran sharaf: Studi pada mahasiswa kelas A Pendidikan Bahasa Arab 2021 UIN Malang - Anwar, Muhammad Rosihan (Maliki Interdisciplinary Journal, 2024)
This research aims to analyze the implementation of the concept map method in learning sharaf in class A Arabic Language Education 2021 at UIN Malang. This study used descriptive qualitative method. The result of this research is that the concept map method began to be applied in the second and third semesters. This implementation begins when the lecturer gives the task of studying and understanding the material next week. After that, students are asked to provide understanding results through a concept map summary. After that, the assignment is submitted in e-learning with a deadline the day before the lecture starts. The concept maps that students have created will become material for discussion together in class. The implementation of the concept method for Sharaf learning in class A Arabic Language Education 2021 really helps students to understand Sharaf science course material because students are required to learn, be creative and disciplined. The obstacles experienced were different educational backgrounds, lack of seriousness in carrying out assignments, and unsuitable teaching methods.